Plant-associated Bacillus and Pseudomonas antimicrobial activities in plant disease suppression via biological control mechanisms - A review - Dimkić, Ivica; Janakiev, Tamara; Petrović, Marija; Degrassi, Giuliano; Fira, Djordje (Physiological and molecular plant pathology, 2022)
Biocontrol strains from the genera Bacillus and Pseudomonas and their bioactive secondary metabolites may be considered beneficial for plant health, since they act through several mechanisms, including direct antibiosis, plant growth promotion and the induction of systemic resistance in the plant hosts. These beneficial bacteria have been proven to be very active against bacterial and fungal phytopathogens, nematodes and different insects. Direct antibiosis, an induced immune system response (ISR) in the host plant and competition for nutrients and space are the most common biocontrol potential of these genera. Species belonging to the Bacillus genus are commonly considered ideal due to their rapid growth, ease of handling and excellent colonizing properties. These endospore‐forming Bacillus strains are capable of suppressing and inhibiting plant pathogens, both indirectly by competing with the pathogens for a niche or nutrient requirements, or directly by producing various lipopeptide compounds such as iturin, surfactin and fengycin, which are active on many plant pathogens. Furthermore, they are also capable of inducing systemic resistance in plants through the production of volatile substances including alcohols, aldehydes, aromatics, sulfides and ketones. Lipopeptides, polyketides and volatiles from Bacillus spp. can stimulate the expression of genes coding for pathogenesis-related (PR) proteins and other defense-related proteins in the plant hosts through the activation of jasmonic acid (JA), salicylic acid (SA) or ethylene (ET) signaling pathways. In addition, inhibition of quorum sensing in competitive bacteria and the capability to downregulate expression of genes involved in mycelial growth, penetration, sporulation and the virulence of a fungal pathogen is another property of Bacillus strains and their volatiles. The Pseudomonas genus is rich in species with the potential for biocontrol with positive effects on plant welfare, which actively participate in complex plant-pathogen-antagonist interaction. The most common molecules involved in this mechanism are, among others, 2,4‐diacetylphloroglucinol, phenazine‐1‐carboxylic acid, phenazine-1-carboxamide, pyoluteorin and pyrrolnitrin. Cyclic lipopeptides from Pseudomonas spp. such as nunamycin, nunapeptin, brasmycin and braspeptin were intensively studied as agents for plant biocontrol and biostimulation in agriculture. Nunamycin, nunapeptin, brasmycin and braspeptin were identified as essential in the antifungal role. Furthermore, phenazines, sessilins and orfamides were shown to have additive roles in the suppression of some fungal diseases. Additionally, Bacillus and Pseudomonas spp. produce chitinases, glucanases and proteases involved in the suppression of many fungal diseases. Their production is mainly induced by the presence of fungal pathogen biomass and their cell wall. This review provides an updated overview of the antimicrobial activity of plant-associated Bacillus and Pseudomonas involved in plant disease suppression via biological control mechanisms, including their molecular basis and direct activity, offering a better understanding in preventing different pests. •Bacillus and Pseudomonas spp. produce wide array of secondary metabolites.•Secondary metabolites are involved in biocontrol and biofertilization mechanisms.•Numerous phytopathogens are controlled by Bacillus and Pseudomonas isolates.•Molecular mechanisms of biocontrol activity are discussed.